1998
DOI: 10.1111/j.1600-051x.1998.tb02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between C‐telopeptide pyridinoline cross‐links (ICTP) and putative periodontal pathogens in periodontitis

Abstract: Crevicular fluid pyridinoline cross-linked carboxyterminal telopeptide of type 1 collagen (ICTP) is predictive for future alveolar bone loss in experimental periodontitis in dogs. The present study sought to relate ICTP to a panel of subgingival species in subjects exhibiting various clinical presentations such as health (n=7), gingivitis (n=8) and periodontitis (n=21). 28 subgingival plaque and GCF samples were taken from mesiobuccal sites in each of 36 subjects. The presence and levels of 40 subgingival taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 28 publications
6
45
0
Order By: Relevance
“…Previous reports analyzing ICTP levels in GCF have consistently compared total amounts of GCF versus concentration, and the most predictive results were found when total amounts were normalized by the time of collection. [8][9][10][11] The mean total amount of ICTP present at baseline in this cohort of periodontitis subjects was similar to previous investigations that measured ICTP levels in untreated periodontitis subjects. 8,11,27 In contrast, Palys et al 9 reported lower ICTP levels among a group of previously treated periodontitis subjects participating in a periodontal maintenance program.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous reports analyzing ICTP levels in GCF have consistently compared total amounts of GCF versus concentration, and the most predictive results were found when total amounts were normalized by the time of collection. [8][9][10][11] The mean total amount of ICTP present at baseline in this cohort of periodontitis subjects was similar to previous investigations that measured ICTP levels in untreated periodontitis subjects. 8,11,27 In contrast, Palys et al 9 reported lower ICTP levels among a group of previously treated periodontitis subjects participating in a periodontal maintenance program.…”
Section: Discussionsupporting
confidence: 86%
“…Talonpoika and Hämäläinen 27 utilized a similar stratification scheme based upon probing depth and also reported significantly higher ICTP levels among untreated periodontitis subjects at sites with deep PD (i.e., 4 to 10 mm). However, Palys et al 9 reported no significant differences in ICTP levels at sites exhibiting different PD among a cohort of treated periodontitis patients. These investigators did detect higher levels of ICTP at shallow sites in both a gingivitis and periodontitis cohort compared to periodontally healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One particular example can be using DNA probes to differentiate healthy, gingivitis, and periodontitis subjects using DNA-DNA hybridization techniques (Palys et al, 1998).…”
Section: Dna As a Biomarker Binding Platformmentioning
confidence: 99%